Laparoscopic adrenal cystectomy - report of two cases (Journal of Chittagong Medical College Teachers' Association, 2009)
Key words: laparoscopic; adrenal cystectomydoi: 10.3329/jcmcta.v19i1.3854Journal of Chittagong Medical College Teachers' Association 2008: 19(1):50-53